Aprendizagem nas organizações: uma análise de grupos multifuncionais de empresas do ramo automotivo - Silva, Marcelo Ribeiro (2013)
The objective of this thesis is to understand the learning processes that occur in crossfunctional groups in a perspective of Advanced Planning Product Quality (APQP) in automotive companies. The specific objectives seeks to identify and describe the constitution process of cross-functional groups and its relationship to learning; identify and describe the methodologies used inside cross-functional groups and its relationship to learning; identify, describe and discuss the factors that difficult the learning process inside cross-functional groups; identify, describe and discuss the factors that facilitate the learning process of crossfunctional groups and identify, describe and discuss the moments which there was evidence of group and collective learning. The theoretical framework proposed is designed of individual and collective learning developed by Nancy Dixon and team learning from the perspective developed especially in studies of Amy C. Edmondson and colleagues. The field research was developed in a qualitative, descriptive and interpretative way. It is also considered exploratory because the phenomenon of learning in work groups has been a topic that reveals little knowledge accumulated and systematized. Considering that research begins with a contextual-interpretive perspective, was proposed as the method qualitative case-study to observe, explore, interpret, understand and discuss issues related to learning processes. In order to achieve the proposed objectives and answer the research question, respondents were members of cross-functional groups of two distinct organizations (Alfa and Beta), three groups per company, totaling nineteen interviewees. Moreover, the non-participant observation is also a strategy to collect data. In order to structure, organize and analyze the data, was employed the templates analysis method, offered by Nigel King, that consist in the use of a priori codes derived from the theoretical framework. The results showed that, since there is psychological safety established, both team and collective learning occurs when the entire group, converging the members conflicts and discussions on consensus. Furthermore, the learning process is facilitated since the group constitution, mainly due to the mobility of its members, the manager's role as a catalyst of information, working methodologies employed in the two organizations, the Transitive Memory Systems, the "corridors", the practice of consulting the functional areas by its members, the existence of international forums, the actual physical arrangement of the companies surveyed, the moral support practiced in the core community, the investment of financial resources for the development of ideas members, the recognition of the expertise of the members, learning through practice of collective work, the willingness of participants to learning, among others. The indications for future studies encompass elements as macro-organizational culture and meso-organizational diversity and its influence on group learning, which are also limiting aspects of this research.